Business Process Analysis and Improvement in Selling Process Using Business Process Modelling Notation (BPMN) at Locarvest - Amalina , Fadhilah; Handayati, Yuanita (KnE Social Sciences, 2020)
This research is conducted in Locarvest. Established in 2015, Locarvest is an online platform company that selling agricultural products based in Bandung. They see the importance of agricultural products for humans and people who like to shop online as an opportunity for them to sell local agricultural products online. Currently, they have been developing a website to change their selling platform which will be launched soon in the late of July 2019. They assume that the website can create a simpler selling process. However, they do not have their written business process where many companies have become increasingly interested in business processes due to the need for effective and efficient activities (Dave, 2017). In here, the objectives of this research are to analyze and model the current business process of Locarvest and propose a new business process to solve Locarvest’s current problem using the concept of Business Process Management (BPM) and the design is modeled using Business Process Modelling Notation (BPMN). To model the current business process, interviews with the employees of Locarvest and observation in the office were conducted. The result of this paper is proposing some improvements within the business process by eliminating some activities and create some new activities for Locarvest. The design also has been approved by the employees of Locarvest. Keywords: Business process, Business Process Management, Business Process Modelling Notation, case study, agriculture